Digital Literacy through a Web-Based Application: Addressing Polarization and Promoting Social Integration among Islamic Senior High School Students - Fitriah Artina; Muhammad Amin; Maria Lufransiya Bribin; Nurlaili Handayani (ASEAN Journal of Educational Research and Technology, 2027)
Digital literacy encompasses not only technical skills but also an understanding of social dynamics such as polarization and the need for social integration in digital environments. This study aims to examine the effectiveness of a web-based Mobile Polarization and Social Integration application in improving students’ digital literacy. A quasi-experimental design with a control group was employed, involving students from an Islamic senior high school. Data were collected using a validated test and analyzed through comparative statistical methods. The application significantly enhances students’ digital literacy and supports their awareness of polarization and social integration. This study highlights the potential of web-based learning applications to strengthen digital citizenship and encourage responsible and inclusive participation in digital spaces.